Antinociceptive and anti-inflammatory activities of Schefflera octophylla extracts. (2nd August 2015) - Chen, Yanfen; Tao, Shuhong; Zeng, Fanlin; Xie, Luwei; Shen, Zhibin
Abstract: Ethnopharmacological relevance: Schefflera octophylla (Lour.) Harms, a traditional Chinese herb mainly distributed in Southeast Asia, is extensively prescribed to alleviate pain and treat rheumatoid arthritis (RA), influenza, throat swelling, pain, etc. In this paper, the antinociceptive and anti-inflammatory activities of the ethanol extract and its five different polar fractions of this plant were evaluated. Furthermore, the anti-rheumatoid arthritis activity of the ethanol extract and its active fraction (CHCl3 fraction) were evaluated. And the chemical constituents of the CHCl3 active fraction displayed significant antinociceptive and anti-inflammatory activities were investigated. Materials and methods: Antinociceptive and anti-inflammatory activities were investigated by hot plate test, acetic acid-induced abdominal writhing test and formalin test, xylene-induced ear edema test. The anti-rheumatoid arthritis activity was evaluated through the model of adjuvant-induced arthritis (AA) in rats, paw swelling, pain response, arthritis index and histopathological changes of ankle, the levels of TNF-α, IL-1β, IL-6 and rheumatoid factor (RF) of rats were detected. The chemical constituents of the CHCl3 fraction were isolated using chromatographic techniques. Their structures were elucidated by spectroscopic data analysis. Results: The results showed that the ethanol extract of S. octophylla has significant dose-dependent anti-inflammatory and antinociceptive activities. And its five different polar fractions especially the CHCl3 fraction significantly inhibited the abdominal writhing induced by acetic acid and ear edema induced by xylene, also increased pain threshold in hot plate test in 120 min and reduced ticking times in formalin test. The ethanol extract of S. octophylla and the CHCl3 fraction demonstrated an anti-RA effect in a dose-dependent manner. The levels of TNF-α, IL-1β and IL-6 in ethanol extract (600 mg/kg) and CHCl3 fraction (300 mg/kg) groups were significantly lower than those of the model group. The chemical constituents study of the CHCl3 fraction from S. octophylla led to six triterpenoids which were identified as taraxerone (1 ), 3-epi-taraxerol (2 ), aleuritolic acid (3 ), 3-oxofriedelan-28-oic acid (4 ), 3β, 19α -dihydroxy-urs-12-ene- 24, 28-dioic acid (5 ) and asiatic acid (6 ). Compounds1 –5 were obtained from this plant for the first time. Conclusion: This study proved the antinociceptive, anti-inflammatory and anti-rheumatoid arthritis activities of S. octophylla. Triterpenoids obtained from its CHCl3 fraction may be responsible for those activities. These results could support the fact that S. octophylla is used traditionally to cure inflammatory and pain diseases. Graphical abstract: